A Semiotic Pragmatic Analysis of Signs on Billboard Advertisement - Sondang Manik; Sahlan Tampubolon; Immanuel Padang (Jurnal Scientia, 2022)
Semiotic pragmatic is a branch of semiotic inquiry which study “the relationship between signs and interpreter or users” use of signs. Pragmatics specifically deals with the aspects of communication specifically situational functions that underlie speech. Therefore, one of the goals of semiotic analysis is to provide analytical methods and thinking and coping frameworks for misreading or misinterpreting the meaning of a sign. The researcher uses Roland Barthes' semiotics approach, and also uses John Space 2019, used as a methodology for peeling and deciphering elements of meaning signs found in advertisements and then interpreting them. The writer found out the message implied on billboard advertisements, 1. by focusing on the product, visually, and putting the tag line verbally, 2. By using popular artists’ endorsement on the product 3. Put the context visually first and making interpret the verbal message, 4. make the context on the Billboard, when to enjoy the product 5. The writer found the type of connotative meaning mostly uses friendly connotation 0,86% the hard connotation0,0 4%, high connotation 0.08%, dangerous connotation 0.04% means most Billboard advertisements use friendly connotation 0,86%, friendly connotation by using slang words, or colloquial sentences, that make the reader as friends. To find out the myth implied in those billboard advertisements, which is where when the connotation aspect becomes popular thought in society, then Myth naturalizes events: it transforms history into nature. myth is a semiological system that has the pretension of transcending itself into a factual system.